2001
DOI: 10.1016/s0893-133x(01)00250-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Olanzapine Treatment on Monoamine Metabolite Concentrations in the Cerebrospinal Fluid of Schizophrenic Patients

Abstract: The mechanism of action of both typical antipsychotics and the atypical antipsychotic, clozapine, may be related to the (changing) interaction of dopamine and serotonin in schizophrenia. This study examined the effect of olanzapine in schizophrenic patients on cerebrospinal fluid (CSF) metabolites of dopamine (homovanillic acid, HVA) and serotonin (5-hydroxyindoleacetic acid, 5-HIAA). Twentythree male schizophrenic patients, who were drug-free for at least 2 weeks (mean drug-free period of 35 days Ϯ 43; median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 70 publications
0
21
0
4
Order By: Relevance
“…Additionally, while 5-HIAA and HVA levels alone could not predict treatment outcome, a low HVA/5-HIAA CSF ratio was significantly associated with better response to clozapine and typical antipsychotics in several studies (Pickar et al, 1992;Kahn et al, 1993a;Risch and Lewine, 1993;Szymanski et al, 1993;Lieberman et al, 1994;Risch, 1995). These results suggested that the antipsychotic effect is associated with changing dopamine function relative to 5-HT function, rather that changing dopamine or 5-HT function per se (Scheepers et al, 2001b).…”
Section: Serotonin Metabolites In the Cerebrospinal Fluidmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, while 5-HIAA and HVA levels alone could not predict treatment outcome, a low HVA/5-HIAA CSF ratio was significantly associated with better response to clozapine and typical antipsychotics in several studies (Pickar et al, 1992;Kahn et al, 1993a;Risch and Lewine, 1993;Szymanski et al, 1993;Lieberman et al, 1994;Risch, 1995). These results suggested that the antipsychotic effect is associated with changing dopamine function relative to 5-HT function, rather that changing dopamine or 5-HT function per se (Scheepers et al, 2001b).…”
Section: Serotonin Metabolites In the Cerebrospinal Fluidmentioning
confidence: 97%
“…But all of these measure have been found to be associated with decreased HVA CSF levels as well (ibid. ; Scheepers et al, 2001b).…”
Section: Serotonin Metabolites In the Cerebrospinal Fluidmentioning
confidence: 99%
See 3 more Smart Citations